Thinning and final cutting control in black locust (Robinia pseudoacacia L.) stands: a methodological approach – Short communication - Rédei, Károly; Honfy, Veronika; Ábri, Tamás (Acta Agraria Debreceniensis, 2024)
Planning, implementing and inspecting forestry operations require more extent application of certain assessment methods. These methods may need to be improved and, in some cases, their simplification is necessary in order to ease their usage in practice. Knowledge and application of auxiliary tables and functions, data on volume and methods to estimate yields are needed for the planning of any kind of forestry operations, depending on the level of planning. The main purpose of this paper is to propose relatively rapid and simple methods to estimate the volume at thinning and final cutting, and the gross above ground volume at the harvest of black locust (Robinia pseudoacacia L.) stands, as well as to introduce tending operation models tailored for black locust. All these measures could be beneficial to forest authorities and foresters who are responsible for planning and production.